A review of recent developments in kenaf fiber/polylactic acid composites research - Khan, Abir; Sapuan, S. M.; Siddiqui, Vasi Uddin; Zainudin, E. S.; Zuhri, M. Y. M.; Harussani, M. M. (Elsevier, 2023)
Kenaf fiber has recently garnered exponential interest as reinforcement in composite materials across diverse industries owing to its superior mechanical attributes, ease of manufacture, and inherent biodegradability. In the discourse of this review, various methods of manufacturing kenaf/Polylactic acid (PLA) composites have been discussed meticulously, as delineated in recently published scientific literatures. This paper delves into the chemical modification of kenaf fiber, examining its consequential impact on tensile strength and thermal stability of the kenaf/PLA composites. Further, this review illuminates the role of innovative 3D printing techniques and fiber orientation in augmenting the mechanical robustness of the kenaf/PLA composites. Simultaneously, recent insightful explorations into the acoustic properties of the kenaf/PLA composites, underscoring their potential as sustainable alternative to conventional materials have been reviewed. Serving as a comprehensive repository of knowledge, this review paper holds immense value for researchers aiming to utilize the capabilities of kenaf fiber reinforced PLA composites.